Sino-Russian Rapprochement and Its Impact on Global Power Dynamics - ANDREEA-EMANUELA DRĂGOI; ANA-CRISTINA BÂLGĂR (Global Economic Observer)
Currently, the debate about Sino-Russian relations is on the rise and draws the attention of many international analysts and policy makers. With bilateral cooperation increasing in recent years, an evident rapprochement is now occurring. This article aims at emphasising the common economic and geopolitical interests behind this new-era relationship, taking into account the recent economic and security pressures coming from the U.S. that created a common ground for the two countries, as well as the historical key-role played by trade and investment and by the energy link. Furthermore, the paper will argue the implications that this strategic economic and political partnership has on the transition in the balance of power in a unipolar world (currently led by U.S.) towards a more complex alignment. Having large natural resources, huge territory and a numerous population, both countries remain geopolitical forces in today’s world. After the sanctions, Russia is currently building a strong economic partnership with China (through the Far East Initiative). It is our opinion that this new global power dynamics that sees China and Russia increasingly supporting each other on the world stage could moderate U.S. global influence leading to a new international equilibrium.